Textile reinforced concrete for sustainable structures: Future perspectives and application to a prototype pavilion. (29th January 2020) - Valeri, Patrick; Guaita, Patricia; Baur, Raffael; Fernández Ruiz, Miguel; Fernández‐Ordóñez, David; Muttoni, Aurelio
Abstract: Textile reinforced concrete (TRC) is a cementitious‐based material where reinforcement consists of high‐strength noncorrosive textile fabrics. Due to the use of a noncorrosive reinforcement, cover requirements can be limited to minimum static values and the amount of clinker in the cement can also be notably reduced. In addition, the simplicity to arrange the fabrics in complex formworks makes the material suited for thin shells or folded structures (typically with thicknesses ranging 10–20 mm). Due to the savings in material and to the lower amounts of clinker used for its production, TRC has a higher sustainable potential than conventional reinforced concrete, with a significantly lower CO2 footprint. To encourage an extensive use of TRC in practice, several topics need however further development. They comprise aspects related to the material and structural response of TRC, but also to the design and to the possibilities to integrate TRC within the architecture and building‐physics. In the present research, results of a 4‐year research program on TRC performed by researchers in civil engineering and architecture are presented. The response of the material is first investigated in tension, bending, and shear. On this basis, considerations on the potential of TRC for construction are drawn and an example of application is presented with the construction of a full‐scale pavilion entirely in TRC.